COVID-19 and Comorbidities: Audit of 2,000 COVID-19 Deaths in India - Shaffi F. Koya; Shahul H. Ebrahim; Lekha D. Bhat; Bindhya Vijayan; Salman Khan; Soji D. Jose; Zarin Pilakkadavath; Premini Rajeev; Jinbert L. Azariah (Springer, 2021)
Background: On September 5, 2020, India reported the second highest COVID-19 cases globally. Given India's unique disease burden including both infectious and chronic diseases, there is a need to study the survival patterns of COVID-19. We aimed to describe the factors associated with COVID-19 deaths in the State of Tamil Nadu that has the highest COVID-19 case burden among the Indian states, and to compare deaths among COVID patients with and without comorbidities. Methods: We analyzed the first 1000 COVID deaths (1 March to 26 June 2020) and 1000 recent deaths at the time of analysis (1-10 August 2020). We examined data on facility (public vs private), age, gender, duration of illness prior to and/or during hospitalizations, symptoms, comorbidities and cause of death. We used R statistical program to do the analysis. We compared deaths among patients with and without comorbidities using Wilcoxon rank sum test. p < 0.05 was considered significant. Results: First, we found a shorter time interval from onset of symptoms to death in India than that was reported in the USA and China. Second, young adults without comorbidities had shorter survival from the time of onset of symptoms irrespective of their timing of hospitalization. Third, hypothyroidism is a COVID-19 associated co-morbidity. Longitudinal studies are needed to further assess the thyroid-COVID-19 link. Conclusion: As COVID-19 infection rates are accelerating rapidly in India, it is crucial to sensitize young adults while protecting the elderly and other vulnerable populations.